Challenges and opportunities for capturing local benefits (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
In Morocco, the potential for solar and wind energy generation is enormous and could be exploited for addressing not only energy security concerns, but also pressing social and economic needs. Smart policy design that integrates different policy objectives can have long-lasting effects, stimulating competitiveness across the economy.